Pengolahan Data Masuk dan Keluar Menggunakan PHP dan MySQL - Syifa Irhammi Ramdhania; Ikrar Panji Satrio; M. Dicky Firyal; Afriyani Agustin; Aries Saifudin (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Many companies engaged in fashion and self-service such as Independent Jeans, still use manual processes in storing incoming and outgoing product data, and in the process the system is still inefficient and there may still be errors in storing incoming and outgoing product data. Such as the process of storing incoming and outgoing product data that still uses paper, and the calculations still use a calculator and product entry and exit transactions. So in order to solve this problem, we need a web-based application for processing incoming and outgoing product data that has login features, user lists, added users, supplier pages, brand management, SPG transactions, print transactions, print transactions, transaction lists, report pages. The development process uses the waterfall method, for the language it uses the PHP (HyperText Processor) programming language and MySQL as a DBMS. Application using the waterfall method can facilitate the process of completing the application development process because there are already stages in the method used.